License to loot : the MAI and how to stop it - Vallianatos, Mark; Durbin, Andrea; Chan-Fishel, Michelle (Washington D.C. : Friends Of The Earth, 1998)
MAI staat voor Multilateral Agreement on Investment
Met steun van The Charles Stewart Mott Foundation C.S. Fund en The Foundation for Deep Ecology
Engels
Brochure
Keywords: economie; milieu; investeringen